Synthesis, photochemistry and DNA photocleavage of compounds containing tetrazolethione scaffolds. - Gundugola, Aditya Swaroop V (Kansas State University, 2011)
This dissertation focused on the synthesis of 1-(2-ethynylphenyl)-4-phenyl tetrazole-5-thione derivatives 1 and evaluating their potential as a new class of photoactivated DNA cleaving prodrugs. We hypothesized that light activation of 1 would cause the decomposition of the tetrazolethione ring system to enyne-carbodiimide 2 with simultaneous loss of dinitrogen and sulfur via 1,3-triplet biradicals 1′, which would be spontaneously followed by Schmittel cyclization to indoloquinolines 3 via benzofulvene type biradicals 2′. The biradicals 1′ and 2′ would have the potential to cause DNA cleavage by abstracting hydrogens from its sugar phosphate backbone, analogous to the mechanism of action of naturally occurring enediyne antitumor antibiotics. Note that our proposed prodrugs contained a 1,4-diaryl tetrazolethione functionality and a direct synthetic route for their construction was lacking in the literature despite their wide spread applications. Therefore, our initial efforts were directed towards developing a general strategy to obtain these ring systems. We employed a highly versatile and efficient copper mediated N-arylation to first obtain a series of 1,4-diaryl tetrazol-5-ones which were thionated with Lawesson’s reagent to afford the corresponding 1,4-diaryl tetrazole-5-thiones in moderate yields. Specifically, the synthesis of 1 involved Sonogashira coupling of the obtained 1-(2-bromophenyl)-4-phenyl-1H-tetrazole-5(4H)-thione with the appropriate ethynyl compounds (Chapter 2). Since the tetrazole ring is an important structural component in many biologically and medicinally relevant compounds, we were interested in evaluating the anticancer activity of these compounds in the absence of photochemical activation. The moderate IC50 values against leukemia and breast cancer cell lines showed that the anticancer activity of these compounds prior to photoirradiation was minimal (Chapter 3). Independent studies have shown that the photodecomposition of tetrazolethiones gives carbodiimides via biradicals, and photocyclization of enyne-carbodiimide forms indoloquinoline also via biradicals. However, it was not known whether these two photoreactions could happen sequentially in one pot with one light source from a substrate like 1, generating biradicals 1′ and 2′ which could later be employed for DNA photocleavage as hypothesized. Therefere, we photolysed 1 in acetonitrile, and our results show clean formation of a mixture of enyne-carbodiimides and indoloquinolines via biradicals 1′ and 2′ (Chapter 4). Finally, we investigated DNA photocleavage by 1 at 350 nm and our results showed significant DNA cleavage in concentrations as low as 100 μM (Chapter 5).
Keywords: Ethynyl; Tetrazolethiones; Novel chemotherapeutic drugs; Chemotherapy; Photoactivation; Biradicals; Chemistry (0485)